Chemical Composition of Groundnut Plant: Its Critical Growth Stages as Influenced by the use of Phosphateic and Potassic Chemical Fertilizers - Khamparia, N.K. (Asian Journal of Chemistry, 2010)
A field experiment was conducted in sandy loam typic chromustert soil with increasing doses of phosphorus with potassium applied to groundnut as a test crop. Groundunt crop responded remarkably to the application of phosphorus @ 30 and 60 kg P2O5 ha -1 applied through single superphosphate significantly increased the dry matter yield at 50 DAS and flowering stages over control. Similarly, artificial supplementation of potassium @ 10 and 20 kg K 20 ha-1 in the form of muriate potash significantly and linearly affected the dry matter yield at 50 DAS and flowering stages over no treatment. Progressive doses of phosphorus application significantly enhanced the N, P, K, Ca, Mg uptake at 50 DAS and flowering stages. Similarly, increasing trends in uptake of above plant nutrients were observed with the addition of increasing weights of potassium. Higher levels of application contributed additional increment in promoting the uptake as compared to lower levels and control in both the growth stages. Interaction between P and K was found to be positively affected in increasing dry mailer yield and N, Ca and S uptake in both the stages.